A New Concept for Mobile Environmental Education - Ruchter, Markus (Schriftenreihe des Instituts für Angewandte Informatik - Automatisierungstechnik, Universität Karlsruhe (TH), 2007)
The new concept for mobile environmental education extends the traditional media-based environmental interpretation by means of a mobile context-aware computer. This mobile nature guide system can assist its user during self-determined exploration by adapting its presentation to the usage situation, preferences and current environmental conditions. The impact of the prototype mobile nature guide on environmental literacy and user satisfaction has been compared to traditional media in the field.